The role of hedonic motivation, consumer lifestyle, and store environment in driving impulsive buying - Sriyanto, Agus; Anggara, Dian Sandi; Haryanto, Ifan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This research aims to determine the influence of hedonic shopping motivation, shopping lifestyle, and store atmosphere on impulse buying among customers of the Aeon Mall BSD City department store. Impulse buying refers to consumer behavior where purchases are made spontaneously without prior planning, often driven by external factors or momentary emotions. The variables examined include hedonic shopping motivation, which refers to the consumer's drive to shop for enjoyment or entertainment; shopping lifestyle, which reflects an individual's habitual shopping patterns and preferences; and store atmosphere, encompassing physical environmental elements of the store such as lighting, layout, music, and scent. Data collection was conducted through a questionnaire distributed to 100 respondents selected using simple random sampling. The data was analyzed using SPSS version 20 to examine the relationship between the independent variables and impulse buying behavior. The results of this study indicate that hedonic shopping motivation significantly affects impulse buying, suggesting that the higher the motivation for enjoying the shopping experience, the greater the likelihood of making unplanned purchases. Additionally, shopping lifestyle was found to have an effect on impulse buying, with individuals who embrace a shopping-oriented lifestyle being more likely to engage in impulsive buying behavior. However, the analysis revealed that store atmosphere did not have a significant impact on impulse buying, indicating that the physical environmental factors of the store do not necessarily serve as key triggers for spontaneous purchases. This research provides valuable insights for retail management in designing more effective marketing strategies to encourage impulse buying behavior among consumers.